Who Gets to Breastfeed? A Narrative Ecological Analysis of Women's Infant Feeding Experiences in the UK - Thomson, Gill; Ingram, Jenny; Clarke, Joanne; Johnson, Debbie; Jolly, Kate (Frontiers in Sociology, 2022)
The early postnatal period is a critical period in women’s infant feeding journeys, often marked by high levels of unintended breastfeeding cessation. Previous research has argued that infant feeding should be perceived within a complex system whereby factors operating at different ecological levels (i.e., individual, social/community networks, cultural/institutional) interact to affect individual behaviours. However, currently, more work needs to be done to implement an ecological approach in breastfeeding programs. We adopted a complex-systems lens approach to explore how multi-level factors – individual, mother-infant dyad, health service, family and social networks, and wider community infrastructure - interacted with women’s motivations and experiences of breastfeeding. We undertook a secondary analysis of 24 women’s interviews; all the women had a strong antenatal intention to breastfeed and were expecting their first baby. The interviews were collected during the UK-based Assets-based feeding help Before and After birth (ABA) feasibility trial when their infant was aged between 4-21 weeks. Categorical content analysis was used to explore the interrelationships between key factors and to identify different infant feeding typologies. Two different typologies emerged: ‘disappointed’ (n=7) and ‘by hook or by crook’ (n=17). ‘Disappointed’ women had stopped breastfeeding early; women classified as ‘by hook or by crook’ continued breastfeeding despite facing challenges. Sociodemographic, social, and service level differences between the typologies were noted. ‘Disappointed’ women were more likely to be younger, White-British, to have considered mixed-feeding antenatally and experienced negative breastfeeding support from healthcare professionals and personal networks. Infants of ‘disappointed’ women were more likely to have received unexpected ‘top-ups’ and to be perceived as having infant feeding difficulties. Women classified as ‘by hook or by crook’ were just as likely as ‘disappointed’ women to experience birth-related complications, but demonstrated more proactive help-seeking behaviours, had positive experiences of personal/professional support and accessed wider support. While further research is needed to consolidate and/or refute the typologies, the ecological approach shifts the focus away from mothers’ decisions to consider the multi-level factors that need to be in place to enable women to breastfeed successfully. Further work to encourage help-seeking behaviours and towards improving facilities, support, and services is needed.